An Analysis of Code Mixing as Found in Livy Renata's YouTube Channel - Natasyah, Jeni; Jufrizal, Jufrizal (Universitas Negeri Padang, 2024)
This study focused on the code mixing in YouTube channel used by Livy Renata which analyzed the types and levels. This research applied descriptive qualitative method, which describes the data that researcher collected form of words, phrases, sentences that contain other language mixtures. The data were code mixing utterances in the form of word, phrase, and sentence uttered by Livy Renata in her YouTube Channel. The results of the research on the type of code mixing used Hoffman's theory (1991) found 345 data collected, there were three types of code mixing in Hoffman's theory. They were intra-sentential code mixing, intra-lexical code mixing, and involving change of pronunciation. Based on the analysis of the level of code mixing used the theory of Mckay & Hornberger (1996) found 320 data, there were two levels of code mixing, which were the level of lexical and level of syntactic.